Determining lecturer performance: Analysis of competence, motivation, and self-efficacy through remuneration - Widana, I Dewa Ketut Kerta; Susanto, Primadi Candra; Sadipung, Theresia Oktavia; Pujiati, Herni (Goodwood Publishing, 2025)
Purpose: This study aims to develop hypotheses for future research by reviewing the relationships between competence, motivation, self-efficacy, remuneration, and lecturer performance. ResearchMethodology: A descriptive qualitative approach was employed through a literature review. Secondary data were collected from academic databases including Scopus, Web of Science, Taylor & Francis, Springer, Elsevier, SINTA, DOAJ, and Google Scholar. One empirical study was selected for each variable category to support the review. Empirical findings from the literature were analyzed and synthesized to identify patterns and construct theoretical relationships. Results: The study reveals ten significant relationships: (1) Competence, motivation, and self-efficacy each positively influence remuneration; (2) All three variables also directly affect lecturer performance; (3) Remuneration has a positive effect on lecturer performance; and (4) Remuneration mediates the effects of competence, motivation, and self-efficacy on lecturer performance. Statistical results from reviewed studies show that competence (? = 0.58), motivation (? = 0.49), and self-efficacy (? = 0.45) have strong direct effects on lecturer performance, with remuneration acting as a significant mediator (p < 0.05). Conclusions: Competence, motivation, and self-efficacy are critical factors influencing both remuneration and lecturer performance. Remuneration plays a mediating role, amplifying these effects. The findings provide a theoretical basis for future empirical testing. Limitations: This review focuses exclusively on individual-level variables, excluding organizational and policy-level influences. The generalization of the findings may be limited by the selection of reviewed studies. Contribution: The study contributes to the development of a conceptual framework on lecturer performance and highlights remuneration as a key mediating variable. It offers new insights into performance-related factors in the Indonesian higher education context.